Human–Bat Relationships in Southwestern Nigerian Communities (2022)
Knowledge on the behavioural pattern of fauna species help to maintain good relationship with captive animals. Chimpanzee behavioural pattern differs in many ways with human interactions. The research focused on the effects of tourist participation on Chimpanzee behavior in a captive environment. Fifty copies of Semi-structured questionnaire were administered to the tourist. Chimpanzee activities and interactions with tourists was carried out using standard focal sampling method at 5 minutes interval for 2 days per week for two months. Data were analyzed using descriptive statistics, Mantel-Haenszel χ2 and Cochran-Mantel-Haenszel (CMH) M2 test. The study reveals that majority of the respondents were males (60%) and were first timers who came for the purpose of relaxation and research. The probability of return visit by the respondents was low, due to poor rating of the Zoo. Most of chimpanzee time was spent resting, sitting and standing (29.5%, 23.2% and 17.0%), respectively. The locomotive and display behavioural pattern were statistically significant (p-value = 0.042 and 0.042) at contact and non-contact level. However, there was no statistically difference with the relieve behavioural pattern exhibited by the Chimpanzee, which indicates that, the relieved behaviour observed was independent of non-contact and contact between the Chimpanzee.